Study on Microbiologically Influenced Corrosion Resistance of Stainless Steels With Weld Seams - Shi, Xianbo; Yang, Ke; Yan, Maocheng; Yan, Wei; Shan, Yiyin (Frontiers in Materials, 2020)
Stainless steels are widely used in various industries due to their desirable combination of mechanical properties and corrosion resistance. However, corrosion of stainless steels was reported seriously on the weld seam areas, and it is not exceptive for microbiologically influenced corrosion (MIC). In the present study, MIC resistance of two austenitic stainless steels (A1, A2 for short) and a duplex stainless steel (D1 for short) with weld seams were comparatively studied by measurement of average and maximum pit depths and electrochemical tests. Experimental results showed that the pit depth on the weld seam was much deeper than that on the base metal for all the stainless steels. The variations of linear polarization resistance (RLPR) values on base metal and weld seam showed that weld seam could promote MIC. Thus the study indicated that the weld seam accelerated the MIC. In addition, A1 steel with higher Cu content showed the best MIC resistance, followed by A2 steel with lower Cu content, and D1 steel without Cu addition exhibited the worst resistance to MIC, indicating that Cu addition in stainless steels is speculated to be beneficial to the MIC resistance. The mechanisms of Cu improving the MIC resistance in the stainless steels were discussed.